Open heavy flavor production at LHCb - Wang Jianqiao (EPJ Web of Conferences)
The LHCb experiment is a dedicated heavy-flavor experiment at the LHC and is uniquely well-suited to studying heavy-flavor production in heavyion collisions. Open heavy-flavor production studies at LHCb provide strong constraints on nuclear parton densities and probe the hadronization process in the hot, dense, nuclear media produced in heavy-ion collisions. Recent measurements of heavy-flavor production in heavy-ion collisions with the LHCb detector are presented, including studies of charm and beauty baryon production.